Matrimonial Property Law in Spain - T. V. Akinfieva (Московский журнал международного права)
The issue of Matrimonial Property is one of the most complicated issues in the Family Law of any country. But the experience of Spain in this field is the brightest example of how diversified and detailed legislation on issue of Matrimonial Property can be in the territory of one state.There is no separate Family Code in Spain and the issues of Matrimonial Property are regulated by the Civil Code of 1889. The regulations of the Civil Code are considered to be the common norms.Besides general norms of Civil Code in Spain there is such a phenomenon as Foral Law which for centuries has been reflecting well expressed realities of way of life as well as historical peculiarities of separate administrative territories which for the last scores of years started to take forms of law. It does not concern the common regional law but the diverse regional law of each separate territory. And the regulations of Foral Law are prevailing over the general norms of Civil Code which are additional in these territories.As far as the general norms regulating Matrimonial Property are concerned there are 129 articles dedicated to it in the Civil Code of Spain.Such a detailed approach to the legal solution of such issues like for example family arrangement in case of divorce is of considerable interest for Russian Family Legislation.